An Ohmic model for electrokinetic flows of binary asymmetric electrolytes. (August 2016) - Persat, Alexandre; Santiago, Juan G.
Abstract: The transport of electrolytes in electric fields is a ubiquitous phenomenon commonly harnessed in microfluidics. A classic leaky dielectric model for flow generated by electric fields accurately predicts electrohydrodynamic transport phenomenon but is valid for millimeter-scale and larger flows and at relatively low ionic strength. Here, we derive and use a modified version of this model to sub-millimeter scales more relevant to microfluidics, where diffusive transport of charged species becomes non-negligible. We formulate a general equation set, the modified Ohmic model, applicable to the transport of binary, asymmetric electrolytes. We leverage this model to describe a variety of microfluidic electrokinetic systems, including DC electroosmosis, alternating current electrokinetics (ACEK) and induced-charge electroosmosis (ICEO), thus highlighting some unifying principles of these flows. Graphical abstract: Highlights: We derive a general model for electrokinetic flows including diffusive currents. We review free charge dynamics and distribution in electric double layers. Our model describes a variety of common electrokinetic flows. We discuss the effects of electrolyte asymmetry in electrokinetic flows.